Youth culture and Islam in Indonesia - Nilan, Pam; Mansfield, Michelle (UI Scholars Hub, 2014)
Indonesian youth culture is sometimes depicted through a moral panic discourse about mixed sex socializing. In this article, the authors challenge that view by presenting some ethnographic material on young Muslim Indonesians of both sexes socialising in an internet caf and gathering during Ramadhan in a mall in Solo, Central Java. Young Indonesians enact everyday youth culture through the negotiation of space, time, and technology within the strong discourse of moral propriety and gender separation advised by contemporary Islam. The intense social bonding between same sex age peers provides security and reassurance for young men and women in the transition to adulthood. Technology is now integral to this bonding.